2007
DOI: 10.1111/j.1479-8298.2007.00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fires on butterfly assemblages in lowland dipterocarp forest in East Kalimantan

Abstract: The post-fire butterfly fauna in lowland dipterocarp forest of the Bukit Soeharto Education Forest (BSEF), East Kalimantan, Indonesia, was assessed during the period November 1998-April 2000 by means of consecutive Malaise trap samples, with supplementary field observations for March-April 1999. A total of 514 butterflies belonging to 61 species and representing six families were caught in the traps. Melanitis leda (Nymphalidae: Satyrinae), Charaxes bernardus (Nymphalidae: Charaxinae), and Danaus genutia (Nymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Since butterflies are often associated with old-growth woodlands, forest edges, and seminatural grassland habitats, they indicate the importance of habitat preservation for conserving regional biodiversity (Kitahara, 2004;Halder et al, 2008). In Southeast Asian tropical rain forests, Hirowatari et al (2007) demonstrated that three generalist butterfly species, Melanitis leda, Charaxes bernardus, and Danaus genutia, could be used as disturbance indicators after fire.…”
Section: Use Of Bioindicators In Forest Man-agementmentioning
confidence: 99%
“…Since butterflies are often associated with old-growth woodlands, forest edges, and seminatural grassland habitats, they indicate the importance of habitat preservation for conserving regional biodiversity (Kitahara, 2004;Halder et al, 2008). In Southeast Asian tropical rain forests, Hirowatari et al (2007) demonstrated that three generalist butterfly species, Melanitis leda, Charaxes bernardus, and Danaus genutia, could be used as disturbance indicators after fire.…”
Section: Use Of Bioindicators In Forest Man-agementmentioning
confidence: 99%
“…Overall, the shift toward reduced dominance by generalists with increasing stand age may be an indication of an increase in niche diversity and stability with stand age, possibly from changes in plant diversity and habitat complexity (Ober, 2007). The greater dominance of generalists in recently disturbed habitats may be attributable to their broad host plant tolerances enabling them to exploit a greater proportion of resources in rapidly changing environments (Hirowatari et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the relative abundance of host plant specialists would increase with stand age among previously logged sites and be highest in old growth stands, with the opposite pattern for generalists. These hypotheses are based on ecological theory predicting a higher proportion of specialist species (which are often numerically rare) in unlogged forests (reviewed in Kitching et al, 2000), the tendency for species assemblages in different successional stages to be unique (Schowalter, 1995;Summerville & Crist, 2002;Hopp et al, 2010), and because variability in plant community composition in early successional environs should favour dietary generalists (Hirowatari et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Lawton et al 1998). In tropical forests, many studies using butterflies have assessed impacts of land use changes such as forest transformation to agricultural land (Harvey et al 2006;Lien and Yuan 2003), silviculture (Stork et al 2003), selective logging (Cleary 2004;Hamer et al 2003), habitat fragmentation (Uehara-Prado et al 2007;Bossart et al 2006) or fires (Hirowatari et al 2007;Cleary and Mooers 2006). However, rarely have the impacts of alien species invasions on butterflies been considered.…”
Section: Introductionmentioning
confidence: 98%